REGIONAL LANGUAGE BACKGROUND AND STUDENTS’ COMMUNICATION STYLES IN A MULTICULTURAL CAMPUS CONTEXT - Dian Pratiwi Tumari; Salsabillah R. Bahsoan; Silfanna J. Podungge; Muziatun Muziatun (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Language is a crucial element in communication used to express ideas and maintain social relationships. Politeness strategies (Brown & Levinson, 1987) play an essential role in protecting the interlocutor's